Gravitational instabilities of nearby star-forming galaxies - Yttergren, Madeleine (My University, 2016)
The dynamics of nearby star-forming galaxies has long intrigued and eluded scientists. Gravitational instabilities are one of the engines of star formation and ”hidden” structures in spiral galaxies, such as bars within bars, ovals and nuclear rings. The radial locations and extent of star-forming regions and other structures can be analysed using the multi-component Q stability parameter of Romeo & Falstad (2013). This parameter accounts for a disc constituted of multiple components, as well as for disc thickness. In this thesis we study the gravitational instabilities of nearby star-forming spiral galaxies focusing on three disc components (atomic hydrogen, molecular hydrogen and stars), as well as their dynamical interplay. We also use another disc instability diagnostic, the characteristic instability wavelength (Romeo & Falstad, 2013), which predicts the sizes of the regions prone to instabilities. Together with the Q stability parameter, we thereby have an appropriate method for analysing galactic discs. We use observational data from four high-quality surveys: THINGS, HERACLES, BIMA SONG and SINGS, which were first analysed and modelled by Leroy et al. (2008). We discover a new ability of the characteristic instability wavelength: the ability to accurately predict the transition between the components dominating the instability. Our analysis also illustrates that the use of higher-resolution data and more accurate modelling, together with the Romeo & Falstad (2013) disc instability diagnostic, may reveal a wider variety of hidden structures in nearby star-forming galaxies
Keywords: Astronomi, astrofysik och kosmologi; Astronomy, Astrophysics and Cosmology